2013
DOI: 10.5194/bg-10-4419-2013
|View full text |Cite
|
Sign up to set email alerts
|

Air–sea exchange of CO<sub>2</sub> at a Northern California coastal site along the California Current upwelling system

Abstract: Abstract. It is not well understood whether coastal upwelling is a net CO2 source to the atmosphere or a net CO2 sink to the ocean due to high temporal variability of air–sea CO2 exchange (CO2 flux) in coastal upwelling zones. Upwelling transports heterotrophic, CO2 enriched water to the surface and releases CO2 to the atmosphere, whereas the presence of nutrient-rich water at the surface supports high primary production and atmospheric CO2 uptake. To quantify the effects of upwelling on CO2 flux, we measured … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…There were 36%, 50%, and 35% of LE, H, and F CO2 , respectively, that passed the quality checks as described above. The similar data gaps were also shown in Ikawa et al [2013] and Podgrajsek et al [2014b] in aquatic flux measurements. About 14% of our data gaps resulted from the occasional malfunction of sonic anemometer during heavy rainfall and snowfall periods.…”
Section: Flux Calculation Quality Assurance/quality Control and Gapsupporting
confidence: 79%
“…There were 36%, 50%, and 35% of LE, H, and F CO2 , respectively, that passed the quality checks as described above. The similar data gaps were also shown in Ikawa et al [2013] and Podgrajsek et al [2014b] in aquatic flux measurements. About 14% of our data gaps resulted from the occasional malfunction of sonic anemometer during heavy rainfall and snowfall periods.…”
Section: Flux Calculation Quality Assurance/quality Control and Gapsupporting
confidence: 79%
“…The computation of eddy covariance was performed half‐hourly, following Ikawa et al . []. Density correction due to sensor heating increased CO 2 flux by 0.039 g C m −2 h −1 [ Burba et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Prytherch et al (2010a) went further and presented a correction method (called the Peter K. Taylor -PKT -method), which has since been used in several publications to correct OP CO 2 fluxes (e.g. Prytherch et al, 2010b;Lauvset et al, 2011;Edson et al, 2011;Huang et al, 2012;Ikawa et al, 2013). Huang et al (2012) reported that the PKT correction did bring some of their CO 2 flux measurements closer to the bulk flux estimate, but found that for small water vapour fluxes the PKT method overcorrected the CO 2 flux and, in some cases, even resulted is a reversal of the flux direction.…”
Section: S Landwehr Et Al: Analysis Of the Pkt Correctionmentioning
confidence: 99%
“…Huang et al (2012) reported that the PKT correction did bring some of their CO 2 flux measurements closer to the bulk flux estimate, but found that for small water vapour fluxes the PKT method overcorrected the CO 2 flux and, in some cases, even resulted is a reversal of the flux direction. Ikawa et al (2013) reported that the PKT correction resulted in increased scatter when applied to coastal tower-based CO 2 flux measurements, and decided not to apply the correction. A selection of the publications mentioned above are also listed in Table 1 together with a brief description of the deployed IRGAs and findings relevant to this contribution.…”
Section: S Landwehr Et Al: Analysis Of the Pkt Correctionmentioning
confidence: 99%